Peri‐procedural code status for transcatheter aortic valve replacement: Absence of program policies and standard practices. Issue 12 (9th August 2022) - Bernacki, Gwen M.; Starks, Helene; Krishnaswami, Ashok; Steiner, Jill M.; Allen, Matthew B.; Batchelor, Wayne B.; Yang, Eugene; Wyman, Janet; Kirkpatrick, James N.
Abstract: Background: Little is known about policies and practices for patients undergoing Transcatheter Aortic Valve Replacement (TAVR) who have a documented preference for Do Not Resuscitate (DNR) status at time of referral. We investigated how practices across TAVR programs align with goals of care for patients presenting with DNR status. Methods: Between June and September 2019, we conducted semi‐structured interviews with TAVR coordinators from 52/73 invited programs (71%) in Washington and California (TAVR volume > 100/year:34%; 50–99:36%; 1–50:30%); 2 programs reported no TAVR in 2018. TAVR coordinators described peri‐procedural code status policies and practices and how they accommodate patients' goals of care. We used data from the Society of Thoracic Surgeons/American College of Cardiology Transcatheter Valve Therapy Registry, stratified by programs' DNR practice, to examine differences in program size, patient characteristics and risk status, and outcomes. Results: Nearly all TAVR programs (48/50: 96%) addressed peri‐procedural code status, yet only 26% had established policies. Temporarily rescinding DNR status until after TAVR was the norm (78%), yet time frames for reinstatement varied (38% <48 h post‐TAVR; 44% 48 h‐to‐discharge; 18% >30 days post‐discharge). For patients with fluctuating code status, no routine practices for discharge documentation were well‐described. No clinically substantial differences by code status practice were noted in Society of Thoracic Surgeons Predicted Risk of Mortality risk score, peri‐procedural or in‐hospital cardiac arrest, or hospice disposition. Six programs maintaining DNR status recognized TAVR as a palliative procedure. Among programs categorically reversing patients' DNR status, the rationale for differing lengths of time to reinstatement reflect divergent views on accountability and reporting requirements. Conclusions: Marked heterogeneity exists in management of peri‐procedural code status across TAVR programs, including timeframe for reestablishing DNR status post‐procedure. These findings call for standardization of DNR decisions at specific care points (before/during/after TAVR) to ensure consistent alignment with patients' health‐related goals and values. Abstract : See related Editorial by Christopher E. Knoepke in this issue.